EFEKTIVITAS METODE MATEMATIKA GASING DALAM MENINGKATKAN KEMAMPUAN PERHITUNGAN DASAR MAHASISWA BARU : STUDI PRA-EKSPERIMENTAL PADA PROGRAM MATRIKULASI UNIVERSITAS INTERNASIONAL PAPUA - Melissa Aeudia Daullu; Ardian Hangga Kelana; Velka Taboka; George Numberi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Basic arithmetic ability is a fundamental competence required for new students, particularly in science and education study programs. However, disparities in secondary education quality in frontier, outermost, and underdeveloped regions (3T) often lead to gaps in mathematical proficiency among new students. This study aims to evaluate the effectiveness of the Matematika Gasing (Easy, Fun, and Enjoyable) method within a bridging program to enhance basic arithmetic learning outcomes for students from Puncak Regency and its surroundings. This research employed a quantitative method with a One-Group Pretest-Posttest design. The sample consisted of 27 new students from various study programs selected using the saturation sampling technique. The instrument used was an integer operation test with a maximum score of 20. Data analysis utilized the Wilcoxon Signed-Rank test and Normalized Gain (N-Gain). The results showed a significant increase in the average score from 6.48 (pre-test) to 12.11 (post-test) with a -value < 0,05. The effectiveness test revealed an N-Gain value of 0.45 (Medium category). These findings indicate that the Gasing method is effective as a pedagogical intervention to restore basic mathematical skills and reduce academic gaps among new students.